LncRNA LINC00963 Promotes Tumorigenesis and Radioresistance in Breast Cancer by Sponging miR-324-3p and Inducing ACK1 Expression - Na Zhang; Xue Zeng; Chaonan Sun; Hong Guo; Tianlu Wang; Linlin Wei; Yaotian Zhang; Jiaming Zhao; Xinchi Ma (Elsevier, 2019)
Upregulation of long non-coding RNA LINC00963 has been observed in several cancer types. In this study, we analyzed the clinical and biological significance of LINC00963 in breast cancer. The key microRNA (miR) mediating the action of LINC00963 was identified. We show that LINC00963 upregulation is correlated with aggressive parameters of breast cancer. Silencing of LINC00963 suppresses the proliferation and tumorigenesis of breast cancer cells, whereas LINC00963 overexpression exerts an opposite effect. Knockdown of LINC00963 enhances DNA damage and oxidative stress and sensitizes breast cancer cells to radiation. Mechanistically, LINC00963 antagonizes the repressive activity of miR-324-3p on ACK1 expression. Clinically, there is a negative correlation between miR-324-3p and LINC00963 expression in breast cancer tissues. Overexpression of LINC00963 or ACK1 rescues the inhibitory effects of miR-324-3p on breast cancer cell proliferation and radiosensitivity. In addition, knockdown of ACK1 attenuates LINC00963-dependent breast cancer growth and tumorigenesis. Taken together, LINC00963 promotes tumorigenesis and radioresistance in breast cancer through interplay with miR-324-3p and derepression of ACK1. LINC00963 may represent a potential target for the treatment of breast cancer. Keywords: cell cycle arrest, growth, lncRNA, radioresistance, ROS